2014
DOI: 10.1165/rcmb.2014-0007oc
|View full text |Cite
|
Sign up to set email alerts
|

A Genomic Signature Approach to Rescue ΔF508-Cystic Fibrosis Transmembrane Conductance Regulator Biosynthesis and Function

Abstract: The most common cystic fibrosis (CF) mutation, ΔF508, causes protein misfolding, leading to proteosomal degradation. We recently showed that expression of miR-138 enhances CF transmembrane conductance regulator (CFTR) biogenesis and partially rescues ΔF508-CFTR function in CF airway epithelia. We hypothesized that a genomic signature approach can be used to identify new bioactive small molecules affecting ΔF508-CFTR rescue. The Connectivity Map was used to identify 27 small molecules with potential to restore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…It has also been reported that miR-138 is decreased in cystic fibrosis airway epithelia. 14 Ramachandran et al discovered that miR-NA-138 regulates cystic fibrosis transmembrane conductance regulator expression through its interactions with the transcriptional regulatory protein SIN3A. 15 Overexpression of miR-138 improved biosynthesis of cystic fibrosis transmembrane conductance regulator-DF508, raising the possibility that manipulating miR-138/SIN3A and their targets might restore the function of misprocessed proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that miR-138 is decreased in cystic fibrosis airway epithelia. 14 Ramachandran et al discovered that miR-NA-138 regulates cystic fibrosis transmembrane conductance regulator expression through its interactions with the transcriptional regulatory protein SIN3A. 15 Overexpression of miR-138 improved biosynthesis of cystic fibrosis transmembrane conductance regulator-DF508, raising the possibility that manipulating miR-138/SIN3A and their targets might restore the function of misprocessed proteins.…”
Section: Discussionmentioning
confidence: 99%
“…After testing 27 small molecules, four were identified that partially rescued maturation and function of Phe508del-CFTR in primary human airway epithelia (HAE), including biperiden, pizotifen, pyridostigmine, and valproic acid. Of these, pyridostigmine showed cooperativity with corrector compound C18 (an analogue of lumacaftor) in improving Phe508del-CFTR function [208].…”
Section: Proteostasis Modulatorsmentioning
confidence: 99%
“…This allowed the synthesis of new molecules with a significant, F508del‐CFTR rescue activity, one of which is a new pyrazine derivative (developed by Novartis) with potent activity as corrector . Another recent study has used an alternative and very elegant approach to find novel correctors – the use of a genomic signature approach that, matching the previous knowledge that miR‐138 enhances CFTR biogenesis and rescues F508del‐CFTR , identified four small molecules that are able to partially correct F508del‐CFTR function in CF epithelia .…”
Section: Introductionmentioning
confidence: 94%